2014
DOI: 10.1039/c3ra44988b
|View full text |Cite
|
Sign up to set email alerts
|

Versatile metal complexes of 2,5-bis{N-(2,6-di isopropylphenyl)iminomethyl}pyrrole for epoxide–CO2 coupling and ring opening polymerization of ε-caprolactone

Abstract: The catalytic activities of metal complexes of 2,5-bis{N-(2,6-diisopropylphenyl)iminomethyl}pyrrole 1 for epoxide-CO 2 coupling and ring opening polymerization (ROP) of 3-caprolactone (CL) were explored.The Zn(II) 2, Cd(II) 3,4 and Cu(II) 5 complexes of 1, in the presence of tetrabutylammonium bromide (TBAB) as co-catalyst, effectively catalyzed the epoxide-CO 2 coupling reaction at 1 atm of CO 2 to produce cyclic carbonates. In addition, the catalytic activities of these complexes (2-5) were investigated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…10) established the living polymerization behavior of these catalysts. 59,60 The observed increase in polymer weight with the increase in [CL]/[catalyst] ratio (low catalyst concentration) further supported this living polymerization nature (Table 3) and is consistent with a small number of active sites at lower concentration of the catalyst. Generally, the polymers obtained in this study exhibited narrow to moderate molecular weight distributions, 1.12-2.47 and 1.79-2.25 for PCLs and PLAs, respectively, indicating some degree of control of the ROP and minimal esterification and epimerization reactions.…”
Section: Kinetics Of Rop Reactions Of E-cl and Lassupporting
confidence: 69%
“…10) established the living polymerization behavior of these catalysts. 59,60 The observed increase in polymer weight with the increase in [CL]/[catalyst] ratio (low catalyst concentration) further supported this living polymerization nature (Table 3) and is consistent with a small number of active sites at lower concentration of the catalyst. Generally, the polymers obtained in this study exhibited narrow to moderate molecular weight distributions, 1.12-2.47 and 1.79-2.25 for PCLs and PLAs, respectively, indicating some degree of control of the ROP and minimal esterification and epimerization reactions.…”
Section: Kinetics Of Rop Reactions Of E-cl and Lassupporting
confidence: 69%
“…Babu et al reported (L diip ) 2 Cu­(MeOH) (L diip = 2,5-bis­(diisopropylphenylimino)­pyrrolide), which interestingly showed bidentate coordination of one and tridentate coordination of the other diiminopyrrolide ligand . Diiminopyrrolide complexes have not been used in lactide polymerization, but diiminopyrrolide yttrium and lanthanide complexes were active in the polymerization of ε-caprolactone. , We speculated that diiminopyrrolide ligands would be able to stabilize the open coordination site in a square-planar copper alkoxide complex, thus avoiding the decomposition reactions observed for copper diketiminates. In the presence of lactide monomer they would likely easily isomerize to bidentate coordination (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…However, we have to admit that the catalytic activity of this polymerization system is lower than that using the Zn complex for the ROP of CL at 25 C (M n ¼ 11 956 g mol À1 , PDI ¼ 1.12, conversion ¼ 98%, 6 h). 24 The chain extension experiment also conrmed the controlled/living nature of the HEBiB/Fe-catalyzed ROP of CL. Fig.…”
Section: Polymerization Kineticsmentioning
confidence: 95%
“…All the listed hydroxyl initiators are suitable for the CL polymerization in this system, yielding the product with moderate to high yields depending on the nucleophilic character and steric feature of the hydroxyl initiator. 24…”
Section: Contributions Of Hydroxyl and Bromidementioning
confidence: 99%
See 1 more Smart Citation